An Leabhar Aifrinn Rómhánach. - Whelton, Marie (Irish Catholic Bishops' Conference / Comhdháil Easpag Caitliceach Éireann, 2018)
The First Sunday of Advent, 2017, marks the use for the first time of the new altar edition in Irish of the Roman Missal. The finished Irish translation is the fruit of a huge collaboration between linguists, theologians and native speakers that endured over fourteen years (2003-2017). The objective of this short article is to outline the background and context of the publication. It is written by Dr Marie Whelton, Chairperson, Coiste Comhairleach na nEaspag Caitliceach um an Liotúirge i nGaeilge and Lecturer at Marino Institute of Education. The full version is available at http://www.liturgy-ireland.ie/.
Keywords: An Leabhar Aifrinn Rómhánach; Translation; Irish-language translation; Aistriúchán; Léann an aistriúcháin; Translation of religious text; Christianity; Missal; Mass-book; Translation studies; Missale Romanum; Téacs Liotúirgeach; Aistriúchán Gaeilge; Translations